2019
DOI: 10.1016/j.jss.2018.09.078
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Reverse Thermal Gel for Minimally Invasive Coverage of Mouse Myelomeningocele

Abstract: Background: Myelomeningocele (MMC) results in lifelong neurologic and functional deficits. Currently, prenatal repair of MMC closes the defect, resulting in a 50% reduction in postnatal ventriculoperitoneal shunting. However, this invasive fetal surgery is associated with significant morbidities to mother and baby. We have pioneered a novel reverse thermal gel (RTG) to cover MMC defects in a minimally invasive manner. Here, we test in-vitro RTG long-term stability in amniotic fluid and in vivo application in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…8,12,14,21 We demonstrated that the RTG can be applied with simple small gauge needle and act as an MMC patch. 8 In addition, the incorporation of biomaterial patches for prenatal MMC closure aims to not only provide a protective barrier but also to help facilitate tissue growth and allow complete skin closure over the defect area. In order to support skin tissue growth over the defect, the RTG should possess scaffolding properties to encourage skin cell growth and proliferation.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…8,12,14,21 We demonstrated that the RTG can be applied with simple small gauge needle and act as an MMC patch. 8 In addition, the incorporation of biomaterial patches for prenatal MMC closure aims to not only provide a protective barrier but also to help facilitate tissue growth and allow complete skin closure over the defect area. In order to support skin tissue growth over the defect, the RTG should possess scaffolding properties to encourage skin cell growth and proliferation.…”
Section: Resultsmentioning
confidence: 83%
“…PSHU-PNIPAAm (RTG) was synthesized as described. 8 Briefly, poly (serinol hexamethylene urea) (PSHU) was synthesized by mixing urea (0.360 g), N-BOC-serinol (1.149 g) 8 precipitated in warm water (45 C), followed by purification in dialysis tubing with molecular weight cut off (MWCO) 12,000-14,000 Daltons (Da) against 9 L of ultrapure water with daily water changes. The purified PNIPAAm-COOH was lyophilized at −45 C for 72 h and stored at RT.…”
Section: Rtg Synthesismentioning
confidence: 99%
See 3 more Smart Citations